TAUẒĪF MAHĀRAH AL-QIRĀAH FI TAḤQĪQ AL-MAKHṬŪṬĀT AL-‘ARABIYYAH - Khalil Mohammad Gbodofu; Abdur-Rasheed Mahmoud Mukadam (ALSINATUNA, 2022)
This study aims at the importance of reading in the investigation of manuscripts, as it requires a wide knowledge, long experience, and a lot of reading. A good reading is the one that eases the difficulties for the investigator, and overcomes the obstacles for him. This paper is a study of the method by which the reading skill is employed in the verification of Arabic manuscripts. After the introduction, the writer spoke briefly about the research method or method, as well as the skill of reading and the verification of manuscripts. Then he sheds light on the role of reading in the verification of manuscripts, and the errors of scribes in manuscripts, then he talks about the investigator's treatment of the text of the manuscript while relying on sources and references related to education and what is related to the verification of manuscripts, referring to them at the end of the research.